A Color-Image Encryption Scheme Using a 2D Chaotic System and DNA Coding. (25th November 2019) - Shakir, Haidar Raad
Abstract : This paper proposes a method of encrypting images with password protection for secure sharing based on deoxyribonucleic acid (DNA) sequence operations and the tangent-delay ellipse reflecting the cavity-map system (TD-ERCS). The initial values of the TD-ERCS system are generated from a user's password, and the TD-ERCS system is used to scramble the pixel locations of the R, G, and B matrices of the original image. Next, three DNA-sequence matrices are generated by encoding the permuted color image such that it can be transformed into three matrices. Then, the TD-ERCS system is employed to generate three chaotic sequences before encoding the DNA into the three matrices. Thereafter, a DNA exclusive OR (XOR) operation is executed between the DNA sequences of the permuted image and the DNA sequences generated by the TD-ERCS system to produce three encrypted scrambled matrices. Finally, the matrices of the DNA sequences are decoded, and the R, G, and B channels are recombined to form an encrypted color image. The results of simulation and security tests reveal that the proposed algorithm offers robust encryption and demonstrates the ability to resist exhaustive, statistical, and differential attacks.